Threat of Extremism &Terrorist Syndicate beyond FATA - Zafar Nawaz Jaspal (Journal of Political Studies, 2010)
The extremism in FATA has been shaped by historical events of the recent and distant past. In the aftermath of 9/11, it facilitated in the formation of transnational terrorist syndicate, which has severe internal and external repercussions for Pakistan’s national interest. The law enforcement agencies have been failing to combat the menace of terrorism effectively due to local and foreign Taliban; Al Qaeda, the Islamic Jihad Union, etc, radicalized recruits popular, political and physical sanctuaries in FATA. This necessitates that Islamabad ought to revise its counterterrorism strategy according to the demands of the asymmetrical warfare